DNA markers for the tomato spotted wilt virus resistance gene (Sw-5) : application in marker-assisted selection - Van Staden, Derick (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1996.